MEDIATISASI AGAMA, POST-TRUTH, DAN KETAHANAN NASIONAL: SOSIOLOGI AGAMA DI ERA DIGITAL - Pertiwi, Ummi Sholihah (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2019)
Moh Yasir Alimi’s book, entitled Mediatisasi Agama, Post-Truth dan Ketahanan Nasional: Sosiologi Agama di Era Digital (Mediation of Religion, Post-Truth, and National Resilience: The Sociology of Religion in the Digital Age) contains critical and solutive reasoning regarding the fact that online media today has mastered the wider community, apart from all kinds of contents that mix between truth and hoaxes. This is because online media/social media have become the commander of where the information comes from. The implication is that the issue of religion, as one of the various problems of community life, is very dependent on and highly influenced by existing online/social media.